A novel approach for engineering efficient nanofluids by radiolysis - Maaza, M.; Khamliche, T.; Akbari, M.; Kana, N.; Tandjigora, N.; Beukes, P.; Genu, A.; Kaviyarasu, K.; K.Cloete, J.; Lekala, M.; Gibaud, A.; Henini, M. (Scientific reports, 2022)
This contribution reports for the first time the possibility of using radiolysis to engineer stable efficient nanofluids which exhibit an enhanced thermal conductivity. The validation was confirmed on Ag-H 2 O and Ag-C 2 H 6 O 2 nanofluids fabricated via g-radiolysis within the mild dose range of 0.95 × 10 3 –2.45 × 10 3 Gray. The enhanced thermal conductivity of Ag-H 2 O and Ag-C 2 H 6 O 2 nanofluids, was found to be g-radiations dose dependent. In the latter case of Ag-C 2 H 6 O 2 nanofluid, the relative enhancement in the temperature range of 25–50 °C was found to be 8.89%, 11.54%, 18.69%, 23.57% and 18.45% for D 1 = 0.95 × 10 3 Gray, D 2 = 1.2 × 10 3 Gray, D 3 = 1.54 × 10 3 Gray, D 4 = 1.80 × 10 3 Gray and D 5 = 2.45 × 10 3 Gray respectively. Yet not optimized, an enhancement of the effective thermal conductivity as much as 23.57% relatively to pure C 2 H 6 O 2 was observed in stable Ag-C 2 H 6 O 2 nanofluids. Equivalent results were obtained with Ag-H 2 O.